2005
DOI: 10.1300/j083v43n04_06
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making in Long-Term Care

Abstract: This article reports findings from a qualitative study of approaches to long-term care decision making used by older adults (N = 52) who continued to reside long-term in the community following nursing facility pre-admission screening. Older adults used different approaches to decision-making (autonomous, collaborative, and delegated) while seeking the ). Rosemary K. Chapin designed and provided overall direction of the operation of the three-year longitudinal study of customers diverted through the CARE progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…They may also have different perspectives about future care and treatment (Retrum, Nowels, and Bekelman, 2012). The existing research also suggests that there are a variety of approaches to health-care decision making, including those focused on autonomy of the elder, as well as those involving collaboration between elders and caregivers (Nakashima, Chapin, Macmillan, & Zimmerman, 2005). Clinicians and researchers have recently emphasized the importance of shared decision-making and patient-centered care as essential components of ethical and humane care for persons with serious illness.…”
Section: Notice In Compliance With Publisher Policy: This Is An Authomentioning
confidence: 99%
“…They may also have different perspectives about future care and treatment (Retrum, Nowels, and Bekelman, 2012). The existing research also suggests that there are a variety of approaches to health-care decision making, including those focused on autonomy of the elder, as well as those involving collaboration between elders and caregivers (Nakashima, Chapin, Macmillan, & Zimmerman, 2005). Clinicians and researchers have recently emphasized the importance of shared decision-making and patient-centered care as essential components of ethical and humane care for persons with serious illness.…”
Section: Notice In Compliance With Publisher Policy: This Is An Authomentioning
confidence: 99%
“…Studies focused on pre-move decisionmaking have highlighted that older adults rarely initiate relocation decisions relying instead on family, professionals or both to determine when relocation is warranted (Fraher & Coffey, 2011;Keister, 2004;Reed, Sullivan, & Burridge, 2003). While self-initiated decisions are presumed to be most desirable, reliance on others can be experienced positively when older adults choose to delegate this decision, do not feel pressured, are involved in decisions associated with the move (e.g., the selection of facilities), and are provided with the opportunity to anticipate the move, even for a short period of time (Fraher & Coffey, 2011;Nakashima, Chapin, Macmillan, & Zimmerman, 2005;Reed et al 2003). Some researchers have suggested that older adults prefer to accept decisions made by others, viewing the decision to relocate as a personal failure (Lee, Woo, & Mackenzie, 2002;Leggett et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The RHQ study involved multiple in-home interviews with each participant over time rather than only one interview per participant, as in the study of Nakashima et al (2004). Project staff also contacted each woman for a monthly telephone conversation when an in-home interview was not scheduled.…”
Section: Methodsmentioning
confidence: 99%
“…Using qualitative methods, some researchers have explored facets of relocation by interviewing older persons who have already relocated (Bekhet, Zauszniewski, & Nakhla, 2009). A few qualitative studies have involved older persons living at home who were on waiting lists for facilities (Nakashima, Chapin, Macmillan, & Zimmerman, 2004; Rutman & Freedman, 1988) -- a factor that could influence perceptions about anticipatory relocation. Thus, the relocation event has been the fulcrum of interest in a process that often has a nebulous beginning.…”
mentioning
confidence: 99%